2009
DOI: 10.1002/ange.200900521
|View full text |Cite
|
Sign up to set email alerts
|

Komplexe mit dativen Bindungen zwischen d‐ und s‐Block‐Metallen: Synthese und Struktur von [(Cy3P)2Pt‐Be(Cl)X] (X=Cl, Me)

Abstract: Ein Platin‐Beryllium‐Addukt (siehe Bild) wurde durch Reaktion von [Pt(PCy3)2] mit BeCl2 erhalten. Die Umsetzung mit Methyllithium führte zur Substitution eines Liganden am Berylliumzentrum. Beide Komplexe wurden strukturell charakterisiert und zeichnen sich durch eine präzedenzlose Zwei‐Zentren‐zwei‐Elektronen‐Bindung zwischen einem Übergangsmetall und Beryllium aus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 42 publications
1
14
0
2
Order By: Relevance
“…Al III and Pt 0 !Be II ), [10] and Fischer et al (Rh I !Ga III ). [11] Armed with this knowledge together with the fact that we successfully synthesized several bimetallic complexes with Sn II !Pd II and Sn II !Pt II interactions, [12] we investigated the reactivity of the kinetically more robust complex cis-[Pt- 2 Cl 2 ] (1, Scheme 2), with the N^C^N-chelating ligand 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 À (hereafter denoted as L), [12c] towards the bridging mt ligand.…”
Section: Ligand These Reactions Yielded Trans-[pt(me)a C H T U N G Tmentioning
confidence: 94%
“…Al III and Pt 0 !Be II ), [10] and Fischer et al (Rh I !Ga III ). [11] Armed with this knowledge together with the fact that we successfully synthesized several bimetallic complexes with Sn II !Pd II and Sn II !Pt II interactions, [12] we investigated the reactivity of the kinetically more robust complex cis-[Pt- 2 Cl 2 ] (1, Scheme 2), with the N^C^N-chelating ligand 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 À (hereafter denoted as L), [12c] towards the bridging mt ligand.…”
Section: Ligand These Reactions Yielded Trans-[pt(me)a C H T U N G Tmentioning
confidence: 94%
“…The increasing number and variety of structurally authenticated transition-metal complexes of boranes, alanes, and gallanes have given more insight into unusual M!ER 3 interactions (E = B, Al, Ga). [2][3] Here, the combination of donor and acceptor moieties within the same ligand architecture, so-called ambiphilic ligands, proved particularly efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous success with the facile formation of "metal-only" Lewis pairs between electron-rich Pt 0 complexes and p-block metals, e. g. in the case of [(Cy 3 P) 2 2 Pt-BeCl 2 ] (1) comprising an unprecedented, electron precise bond between beryllium and a d-block metal [15]. Recent studies showed that related low-valent palladium complexes also show a propensity to act as metal bases towards metal-coordinate boryl and borylene ligands, and therefore behave similar to their platinum congeners [16 -19].…”
Section: Introductionmentioning
confidence: 99%